Experimental and Numerical Study of a Submarine and Propeller Behaviors in Submergence and Surface Conditions - A. Vali; B. Saranjam; R. Kamali (Journal of Applied Fluid Mechanics, 2018)
In this paper, hull/propeller interaction of a submarine model which has a realistic geometry, in submergence and surface conditions has been studied. For this purpose, the computational fluid dynamics (CFD) method has been used to solve the viscous, incompressible, two phase flow field (in surface condition) around a model of the propeller and submarine hull with and without propeller. The rotation of the propeller has been modeled using the sliding mesh technique. For turbulent flow modeling and free surface simulation, the k-ω SST model and the volume of fluid method (VOF) have been used, respectively. Experimental data obtained from test conducted by the authors in M.U.T. towing tank have been used to validate the numerical scheme. Comparing numerical and experimental results shows good agreement. The experimental and numerical results show that operation of the propeller near water surface reduces the thrust coefficient of the propeller comparing to open water condition, so that according to experimental results the maximum relative reduction of the thrust coefficient is 8.95%. In addition, the results indicated the amount of hull resistance coefficient in surface condition is more than submergence condition. According to the thrust reduction and wake factors obtained from the numerical results, it is known that their values in surface condition are less than submergence condition. This research can be used for more realistic investigation of hull/propeller interaction and thus, more accurate powering performance prediction of submarines.